2018
DOI: 10.14527/kuey.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships among Trust in Administrator, Distributed Leadership and School Academic Optimism

Abstract: The purpose of this study was to examine the relationships among trust in administrator, distributed leadership and a school academic optimism based on teachers' perceptions and to examine the mediator role of distributed leadership in the relationship between the levels of trust in administrator and the school academic optimism .The participants were a total of 540 teachers employed in elementary, middle and high schools located in the Kadikoy district of Istanbul. The data were gathered through the "Trust in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Specifically, empirical studies have found trust in the university setting to increase collaboration between student and school (Mitchell, Kensler & Tschannen-Moran, 2018;Abdelmaaboud, Peña, & Mahrous, 2020), academic performance (Ennen, Stark & Lassiter, 2015;Latif, Bunce, & Ahmad, 2021), healthy school climates and quality school life (Hongwidjojo, Monika & Wijaya, 2018;Jones & Afnan, 2019), collective teacher efficacy (Flood & Angelle, 2017), triadic set of interactions and academic optimism (Cansoy & Parlar, 2018), and student identification with school (Mitchell, Kensler, & Tschannen-Moran, 2018).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Specifically, empirical studies have found trust in the university setting to increase collaboration between student and school (Mitchell, Kensler & Tschannen-Moran, 2018;Abdelmaaboud, Peña, & Mahrous, 2020), academic performance (Ennen, Stark & Lassiter, 2015;Latif, Bunce, & Ahmad, 2021), healthy school climates and quality school life (Hongwidjojo, Monika & Wijaya, 2018;Jones & Afnan, 2019), collective teacher efficacy (Flood & Angelle, 2017), triadic set of interactions and academic optimism (Cansoy & Parlar, 2018), and student identification with school (Mitchell, Kensler, & Tschannen-Moran, 2018).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Some research support the results of research on the level of trust in teachers in secondary schools and high schools. Cansoy and Parlar (2018), showed that distributed leadership and trust in the administrator predicted the school academic optimism. Özdemir and Pektaş (2017) also found that there was a positive, significant and moderate relationship between social justice leadership and academic optimism, and that social justice leadership was an important predictor of academic optimism.…”
Section: Result Discussion and Recommendationsmentioning
confidence: 99%
“…Although research has been conducted on many issues related to academic optimism, more research is needed to better understand teacher academic optimism and develop academic optimism theory in schools (Hoy et al, 2006;Hoy & Miskel, 2012). Academic optimism is associated with student achievement, and research has been conducted on many issues related to academic optimism, such as student academic success, professional commitment, factors that contribute to school development, distributed leadership, organizational climate, teachers' academic optimism, social justice leadership, and bureaucratic structure (Ateş & Ünal, 2021;Bevel & Mitchell, 2012;Boonen et al, 2014;Straková et al, 2018;Kurz, 2006;Best, 2014;Cansoy & Parlar, 2018;Kılınç, 2013;Reeves, 2010;Feng & Chen, 2019;Özdemir & Kılınç, 2014). Therefore, determining the characteristics of schools that affect teachers' academic optimism can help us understand why academic optimism differs between schools, determine causal relationships between academic achievement and academic optimism, and find ways to improve teachers' academic optimism.…”
Section: The School's Culture Of Academic Optimismmentioning
confidence: 99%